Zero‐Degree Endoscopic Visualization of the Frontal Sinus Predicts Improved Topical Irrigation Delivery. (11th April 2020) - Spielman, Daniel B.; Kim, Matthew; Overdevest, Jonathan; Gudis, David A.
Abstract : Objective: Management of chronic frontal rhinosinusitis is challenging with high rates of treatment failure, exacerbated by limitations of topical irrigation delivery. We hypothesize that intraoperative zero‐degree visualization of the frontal sinus predicts improved postoperative irrigation penetration. Extending a Draf IIa frontal sinusotomy with a limited resection of the middle turbinate axilla‐agger nasi complex can allow zero‐degree endoscopic visualization of the frontal sinus. This study investigates the change in frontal sinus irrigation delivery after standard Draf IIa frontal sinusotomy versus further resection to achieve zero‐degree visualization. Study Design: This is a prospective cohort study conducted in a surgical skills laboratory. Methods: The extent of irrigant penetration into the frontal sinuses was evaluated in 10 cadaveric frontal sinuses following Draf IIa sinusotomy using a standardized trephine visualization model. Irrigant penetration was assessed by three blinded reviewers using the following scale: 0 = irrigation restricted to nasal cavity; 1 = irrigation reaches frontal recess; 2 = irrigation reaches frontal sinus proper; 3 = irrigation fills entire frontal sinus. These results were compared to irrigation after achieving zero‐degree endoscopic visualization by performing limited resection of the middle turbinate axilla‐agger nasi complex. Results: Irrigant penetration following standard Draf IIa frontal sinusotomy improved after the axilla‐agger nasi complex was resected to achieve zero‐degree endoscopic visualization (median score 2 [interquartile range: 1–2] vs. 3 [interquartile range: 2–3], P < .01). Conclusion: This study demonstrates improved penetration of frontal sinus irrigation following limited resection of the middle turbinate axilla‐agger nasi complex to achieve zero‐degree endoscopic visualization of the frontal sinus as compared to standard Draf IIa frontal sinusotomy. Level of Evidence: N/A Laryngoscope, 131:250–254, 2021